XVI Workshop and Competition for young researchers in the field of statistical physics and condensed matter theory (Condensed Matter Physics, 2015)
The 16th Workshop will be held in Lviv in the Institute for Condensed Matter Physics
on June 9-10, 2016. Its programm will include invited lectures of top experts in statistical physics and
condensed matter theory from Ukraine, short communications of young researchers and contributed
talks of Competition applicants. The 2016 Workshop is dedicated to the famous book by academician
N.N. Bogolyubov “Problems of Dynamic Theory in Statistical Physics” published in 1946.